2018
DOI: 10.1161/jaha.116.005052
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐210 Promotes Accumulation of Neural Precursor Cells Around Ischemic Foci After Cerebral Ischemia by Regulating the SOCS1–STAT3–VEGF‐C Pathway

Abstract: BackgroundNeural precursor cell (NPC) migration toward lesions is key for neurological functional recovery. The neovasculature plays an important role in guiding NPC migration. MicroRNA‐210 (miR‐210) promotes angiogenesis and neurogenesis in the subventricular zone and hippocampus after cerebral ischemia; however, whether miR‐210 regulates NPC migration and the underlying mechanism is still unclear. This study investigated the role of miR‐210 in NPC migration.Methods and ResultsNeovascularization and NPC accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 109 publications
(225 reference statements)
3
29
0
Order By: Relevance
“…These findings are in agreement with studies on the pro-angiogenic role of miR-210 observed in vitro [15,[31][32][33], as well as in miR-210 overexpression studies in mouse models of heart [20][21][22][23], limb [26], and brain ischemia [24,25,34]. Also concordant are studies showing that cord blood-derived cells expressing miR-210 display an increased potential in stimulating angiogenesis upon transplantation Taken together, these results indicate that miR-210 plays a pro-angiogenic role in vivo also in the absence of ischemic injury.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are in agreement with studies on the pro-angiogenic role of miR-210 observed in vitro [15,[31][32][33], as well as in miR-210 overexpression studies in mouse models of heart [20][21][22][23], limb [26], and brain ischemia [24,25,34]. Also concordant are studies showing that cord blood-derived cells expressing miR-210 display an increased potential in stimulating angiogenesis upon transplantation Taken together, these results indicate that miR-210 plays a pro-angiogenic role in vivo also in the absence of ischemic injury.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the role played by miR-210 might be highly context-dependent [6,7]. In different experimental settings, miR-210 has been shown to stimulate the secretion of pro-angiogenic factors, such as VEGF and FGF2 [23,25,36,[38][39][40], which may play a role in the vascular regeneration process also in the context of hindlimb ischemia. Finally, it is worth noting that miR-210 can be secreted into exosomes and, in this way, transferred from cell to cell, further complicating the scenario [20,26,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in accordance with several studies suggesting that miR-210 has a protective function in cardiovascular disease through several mechanisms including SOCS1-STAT3-VEGF-C signaling [30]. Consistent with this finding, blocking the activity of nSMase2 lead to a reduction in miR-210 and abrogated any cardio-protective actions.…”
Section: Discussionsupporting
confidence: 93%
“…17 In ischemic condition, mir-210 plays role as a proangiogenic factor and involves in cell-cycle regulation, DNA damage reconstruction, and neural tissue restoration. [17][18][19]…”
Section: Introductionmentioning
confidence: 99%